Enhancement of electrochemical performance of lithium manganese oxide with graphene for aqueous supercapabattery - Low, J.r.; Lim, H.N.; Ibrahim, I.; Zainal, Z.; Foo, C.Y.; Huang, N.M.; Jiang, Z.T. (Elsevier, 2023)
In this study, we synthesized lithium manganese oxide nanoparticles/graphene nanoplatelets (LMO/GNPs) as the cathode material for a supercapabattery using a hydrothermal method. The addition of GNPs resulted in a 63 and 68 increase in specific capacitance and capacity compared to LMO alone, attributed to the enhanced conductivity and efficient lithium-ion diffusion of GNPs. The LMO/GNPs exhibited excellent rate capability and stability, with 80 capacity retention after 1000 cycles, an energy density of 39.07 Wh kgˆ’ 1 and a power density of 925.40 W kgˆ’ 11, showcasing their potential for supercapabattery applications. These findings highlight the superior performance of LMO/GNPs in the supercapabattery, making it a promising energy storage solution.